Analisis Pemanfaatan Dana Bagi Hasil Pajak Daerah dalam Pembangunan Fasilitas Publik: Studi Kasus Alun-Alun Bangkalan - Malaikatul Jannah Dhuhita Wahyuningtyas; Yuanita Maharani; Mohamad Djasuli (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the impact of the utilization of regional tax revenue sharing funds on the development of public facilities in Bangkalan Regency with a focus on Bangkalan Square as the main public space for the community. The study uses a qualitative approach with a case study method. Data were obtained through field observations, semi-structured interviews, and documentation. Research informants were selected using a purposive sampling technique, namely residents who actively utilize Bangkalan Square facilities. Data were analyzed using the Miles and Huberman interactive analysis model which includes the stages of data reduction, data presentation, and drawing conclusions. The results show that the development of public facilities in Bangkalan Square has a positive impact in the form of improving the function of public spaces, community social activities, and economic activities around the area. However, the utilization of these facilities has not been optimal due to weak management, facility maintenance, and low public understanding of the role of regional taxes in development. This study has implications that local governments need to improve the effectiveness of public fund management, strengthen public facility maintenance, and improve tax education to the community to support sustainable development.